Advanced photonic crystal fiber-based surface plasmon resonance biosensors for transformative RI sensing (Indian Journal of Biochemistry and Biophysics (IJBB), 2024)
This pioneering study unveils an advanced Photonic Crystal Fiber (PCF)-based Surface Plasmon Resonance (SPR) sensor, meticulously engineered for Refractive Index (RI) sensing. With a hexagon lattice of air holes and four gold nanowires enhancing sensitivity, the sensor enables precise RI measurements in biological samples. Geometrical optimization ensures extraordinary sensitivity, with Finite Element Method (FEM) analysis revealing impressive results. Analyte materials such as glucose, ethanol, or proteins like bovine serum albumin (BSA) or immunoglobulin G (IgG) are suggested for use within the RI range of 1.31 to 1.36, crucial for biomedical and environmental sensing. This innovation promises transformative advancements, marking a paradigm shift in RI measurements for diverse scientific and technological applications.